The toxicity of certain cereal proteins in coeliac disease - Cornell, H. J. (1974)
Gliadins from wheat, rye, and oats, and from wheat glutenin were digested with pepsin, trypsin, and pancreatin and the products (PTC digests) chromatographed on sulphopropyl (SP) Sephadex. Fractions eluted near neutral pH from wheat, rye, and oats gliadin digests all had very similar amino acid composition, although the oats fraction was higher in sulphur-containing amino acids. The major amino acids present in all were glutamine/glutamic acid and proline. The amount of fraction eluted near neutral pH from oats gliadin digest was about 13% of that eluted from digests of wheat and rye gliadins. Moreover, the yield of gliadin from oatmeal was only 0·5% compared with 2·4% and 2·8% from rye and wheat flours respectively. The amount of fraction eluted from wheat glutenin digest was about 70% of that obtained from wheat and rye gliadin digests. The fractions eluted near neutral pH from all protein digests were defectively digested by remission coeliac mucosa, and D-xylose excretion tests with the fraction from the wheat gliadin digest (fraction 9) indicated that it is harmful to subjects with coeliac disease, whereas the other fractions of this digest gave no such evidence. The results of the present work indicate that counterpart fractions to fraction 9 obtained from wheat glutenin and rye and oats gliadins may also be important in the aetiology of coeliac disease.